2018
DOI: 10.1002/jpen.1050
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Profiles of Metabolism and Bioenergetics Associated with Innate Immune Hormonal Inflammatory Responses and Amino‐Acid Kinetics in Severe Sepsis and Systemic Inflammatory Response Syndrome in Children

Abstract: A pattern of early longitudinal induction of metabolic-hormones and eHSP72/HSP90α, repression of bioenergetics and innate immunity, hypo-metabolism, and amino-acid kinetics changes discriminate sepsis from SIRS; malnutrition, hypo-metabolism, and persistently increased resistin and adiponectin are associated with poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 38 publications
(41 reference statements)
4
16
0
Order By: Relevance
“…It is the first time that survivin-WT gene or protein expression, as well as total caspases, including active and cleaved forms, are shown to be overexpressed in sepsis and that survivin-ΔEx3, -WT, along with caspase-9 and survivin protein, could better discriminate sepsis among critically ill patients. This finding further enhances results of recent studies, showing that biomolecules, related to repressed bioenergetics and innate immunity 50 , hypo-metabolism and acute hormonal stress 51 , could better discriminate sepsis from SIRS, compared to CRP or lactate.…”
Section: Discussionsupporting
confidence: 84%
“…It is the first time that survivin-WT gene or protein expression, as well as total caspases, including active and cleaved forms, are shown to be overexpressed in sepsis and that survivin-ΔEx3, -WT, along with caspase-9 and survivin protein, could better discriminate sepsis among critically ill patients. This finding further enhances results of recent studies, showing that biomolecules, related to repressed bioenergetics and innate immunity 50 , hypo-metabolism and acute hormonal stress 51 , could better discriminate sepsis from SIRS, compared to CRP or lactate.…”
Section: Discussionsupporting
confidence: 84%
“…Fifth, because the serum concentrations of CRP and albumin were only analyzed at ICU admission, we could not evaluate the changes in CRP, albumin, and CRP/albumin ratio over time. Spanaki et al reported that CRP decreases longitudinally among ICU survivors whereas SIRS survivors showed a longitudinal decline in albumin [ 37 ]. Further studies that investigate the changes in these markers are needed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Other potential protective effects of heme oxygenase induction are a direct modulation of antioxidant genes transcription, an increased production of the tissue mediator carbon monoxide and a decrease in cellular prooxidant heme (42). Bilirubin might also reduce cellular damage through biliverdin reductase action, which has recently been documented to be increased in septic patients (47). Indeed, when bilirubin reacts with reactive oxygen species, toxicity is neutralized and bilirubin is oxidized to biliverdin.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, when bilirubin reacts with reactive oxygen species, toxicity is neutralized and bilirubin is oxidized to biliverdin. Biliverdin can be converted back to bilirubin through biliverdin reductase, and by repeating this cycle, the antioxidative and cytoprotective effect of small amounts of bilirubin is greatly amplified (44, 47). In our study, however, total plasma bilirubin concentrations on the first day of critical illness were associated with PICU mortality in a “U-shape” relationship, in which both low and high levels of bilirubin were associated with higher risk of death.…”
Section: Discussionmentioning
confidence: 99%